2021
DOI: 10.1111/acer.14685
|View full text |Cite
|
Sign up to set email alerts
|

Maternal choline supplementation in a rat model of periconceptional alcohol exposure: Impacts on the fetus and placenta

Abstract: Background: Maternal choline supplementation in rats can ameliorate specific neurological and behavioral abnormalities caused by alcohol exposure during pregnancy.We tested whether choline supplementation ameliorates fetal growth restriction and molecular changes in the placenta associated with periconceptional ethanol exposure (PCE) in the rat.Methods: Sprague Dawley dams were given either 12.5% ethanol (PCE) or 0% ethanol (Con) in a liquid diet from 4 days prior to 4 days after conception. At day 5 of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…As such, the alcohol-exposed fetus may still prioritize the choline supply to support brain development. This argument is further supported by a recent study in a rat model of periconceptional alcohol exposure, which reports improved fetal liver growth in offspring whose mothers receive choline supplementation at 2× and 4× the recommended intake level (Steane et al, 2021). Choline uptake between fetal brain and liver may also differ because the ubiquitous choline transporter SLC44A1, which encodes the choline transporter-like protein 1 (CTL1), is highly abundant in the fetal brain but is expressed in lower amounts in fetal liver (Yuan et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…As such, the alcohol-exposed fetus may still prioritize the choline supply to support brain development. This argument is further supported by a recent study in a rat model of periconceptional alcohol exposure, which reports improved fetal liver growth in offspring whose mothers receive choline supplementation at 2× and 4× the recommended intake level (Steane et al, 2021). Choline uptake between fetal brain and liver may also differ because the ubiquitous choline transporter SLC44A1, which encodes the choline transporter-like protein 1 (CTL1), is highly abundant in the fetal brain but is expressed in lower amounts in fetal liver (Yuan et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies examining periconceptional maternal exposures suggest that EtOH may impact brain weights in the developing offspring ( Steane et al, 2021 ). Further, increased proportional brain to body weight is a reliable indicator of intrauterine growth restriction (IUGR) ( Cortes-Araya et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pathways involving choline, methionine, and folate metabolism are also essential to healthy fetal brain development, and deficits during pregnancy are associated with impaired memory and learning in the offspring [58]. We and others recently reported that choline supplementation improves fetal body, liver, and brain weights in rodent models of FASD [59,60], and consistent with this, we find here that the maternal hepatic content of the one-carbon metabolites methionine and S-adenosylhomocysteine (SAH) are positively correlated with fetal brain weight. Similarly, although alcohol affected the hepatic content of far fewer metabolites in the fetus, the methyl donor S-adenosylmethionine (SAM) and its catabolite 5-methylthioadenosine are negatively correlated with fetal brain weight.…”
Section: Discussionmentioning
confidence: 99%